Lateral Odontogenic Keratocyst Clinically Diagnosed as a Dentigerous Cyst (A case report and literature review) - Haroun, Ghada; Elmurtadi, Ali (Libyan Journal of Dentistry, 2021)
Odontogenic keratocyst (OKC) has been an area of considerable research over the last decades owing to its unique behavior, debated origin, distinctive tendency to recur, and argued nature. In 2005, WHO has adopted the designation of keratocystic odontogenic tumor (KCOT) because of its aggressive nature and tendency to recur, so, it has been long been considered as a benign jaw neoplasm rather than a cyst, though the last classification has returned the OKC back to cyst category. It is not uncommon for OKC to be clinically and radiographically identical to dentigerous cyst which makes the initial diagnosis rather confusing; however, in our reported case another interesting and an unusual feature was the arrival of an intact cyst attached to the neck of an impacted tooth which has further drawn the attention toward the dentigerous cyst, particularly the lateral type. The final diagnosis was made following the microscopic examination of the surgical specimen which was almost convincing and consistent with OKC. The clinical, radiological and histological features of this pathological entity along with brief relevant studies have been discussed.